ANALISIS PENGARUH PERKUATAN WIRE MESH TERHADAP KEKUATAN PILAR DI TAMBANG BAWAH TANAH DENGAN PENGUJIAN SKALA LABORATORIUM - Aldo Azzana Zuhuri; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. Pillars are natural support that serve to hold the material load on it. The development of deeper mines causes the burden received by the pillars will be greater so as to encourage an increase in the dimensions of the pillars to maintain the stability of the work area this will be a challenge to carry out the mandate of Annex VII of the Decree of the Minister of Energy and Mineral Resources No. 1827.K/30/MEM/2018 on Guidelines for the Implementation of Mineral and Coal Conservation. Therefore the pillar requires special reinforcement so as not to collapse during underground mining activities and also maximize recovery. In this study the reinforcement used is wire mesh with a diameter of 0.8 mm then the pillar sample is made of a homogeneous cylindrical material from a mixture of cement and sand with a composition of 1:2, the pillar sample is made close to the strength of coal. The results of this study showed that the installation of strengthening (wiremesh) caused an increase in the strength value on the pillar that was originally a pillar without buffering has a strong uniaxial press of 10.4 MPa and after strengthening the wire mesh obtained 14.65 MPa or increased by 42.5%. This is evidenced by the results of numerical modeling model II shows an increase in strength factor value from the original 1 to 1.3 and decreased horizontal displacement that was originally as far as 0.00024 m to 0.000063 m, the results of pillar strength testing in the laboratory and numerical modeling showed that the increase in strength occurred due to horizontal displacement in the pillar held by wire mesh so that the pillar seemed to experience pressure. Anchoring thus causes horizontal displacement to be smaller compared to horizontal displacement on pillars without wire mesh strengthening.